Antibacterial structure–activity relationship studies of several tricyclic sulfur-containing flavonoids - Bahrin, Lucian G.; Hopf, Henning; Jones, Peter G.; Sarbu, Laura G.; Babii, Cornelia; Mihai, Alina C.; Stefan, Marius; Birsa, Lucian M. (Beilstein Journal of Organic Chemistry, 2016)
A structure–activity relationship study concerning the antibacterial properties of several halogen-substituted tricyclic sulfur-containing flavonoids has been performed. The compounds have been synthesized by cyclocondensation of the corresponding 3-dithiocarbamic flavanones under acidic conditions. The influence of different halogen substituents on the antibacterial properties has been tested against Staphylococcus aureus and Escherichia coli. Amongst the N,N-dialkylamino-substituted flavonoids, those having an N,N-diethylamino moiety exhibited good to excellent antimicrobial properties against both pathogens. Fluorine-substituted flavonoids were found to be less active than those bearing other halogen atoms.
Keywords: antibacterial activity; dithiocarbamates; dithiolium salts; flavonoids; SAR studies